Ex Vivo and In Vivo Imaging Study of Ultrasound Capsule Endoscopy - Lee, John H. (J Med Device, 2020)
Wireless capsule endoscopy (WCE) has revolutionized the capacity for evaluation of the gastrointestinal (GI) tract, but its evaluation is limited to the mucosal surface. To overcome this, ultrasound capsule endoscopy (UCE) that can evaluate the deeper structures beyond the mucosal surface has been proposed and several studies focusing on technology development have demonstrated promising results. However, investigations of the potential for clinical utility of this technology are lacking. This work had two main goals: perform ex vivo and in vivo imaging studies in a swine model to (1) evaluate if acoustic coupling between a capsule with a specific size and GI tract can be achieved only through peristalsis autonomously without any human control and (2) identify key issues and challenges to help guide further research. The images acquired in these studies were able to visualize the wall of the GI tract as well as the structures within demonstrating that achieving adequate acoustic coupling through peristalsis is possible. Critical challenges were identified including level of visualization and area of coverage; these require further in-depth investigation before potential clinical utility of UCE technology can be concluded.